Heterologous expression of a chloride transporter gene AoCLCf from Avicennia officinalis enhances salt tolerance of Arabidopsis plants - Sivamathini Rajappa; Prakash Kumar (Crop Design)
Plant chloride transporters are pivotal for preserving turgor pressure, pH, and cellular ion balance while adapting to salinity stress. We identified a salt-responsive gene, AoCLCf from Avicennia officinalis, which belongs to the chloride channel (CLC) family, and it shares significant sequence similarity with its Arabidopsis counterpart, AtCLCf. Through functional characterization in yeast mutants and Arabidopsis plants, we found that AoCLCf expression was induced primarily in roots under salt stress. Subcellular localization revealed a salt-induced translocation of GFP-AoCLCf from the Golgi apparatus to the plasma membrane. Expression of AoCLCf in the Saccharomyces cerevisiae mutant strain Δgef1 helped to rescue the growth of the mutant at high NaCl concentrations (up to 1.25M). Moreover, constitutive expression of AoCLCf in wild-type Arabidopsis significantly enhanced salt tolerance, as evidenced by increased seed germination rates, and improved seedling growth (greater root and shoot length) under 150 ​mM NaCl treatment. Spectrofluorimetric assays using liposomes embedded with recombinant AoCLCf protein showed that it functions as a chloride channel. These findings underscore the pivotal role of AoCLCf in improving salt stress tolerance through the maintenance of cellular ion homeostasis.